Rancangan Strategi Penanganan Risiko Pada Proyek PLTM (Pembangkit Listrik Mini Hidro) di Indonesia - Sapphiro, Hanif Ramdhani Rachmadi; Nugraha, Made Arya; Widjanarka, Alain; Kurniawan, Jeffrey (Journal of Emerging Business Management and Entrepreneurship Studies, 2021)
This research discusses the design of risk management strategies in MHP projects in Indonesia. MHP is a type of power plant that uses hydropower to turn turbines for generate an electricity. The MHP project involves a large investment with a long construction period.  The length of the construction time, creates an uncertainty factor that impacts on three aspects of the project objectives. The objective aspects of the project are cost, quality, and time. Several MHP projects in Indonesia have underperformed, such as delays in completion time and cost overruns. The risk management process, which consists of risk identification, risk assessment, risk management formulation and risk control, forms the basis of research work. In this study, 23 risks were identified in the MHP project. Fifteen of them have high impact on two aspects and three have high impact on three aspects of project objectives. The results of this study can be used as a guide for risk management in MHP projects in Indonesia. The results of this study can be used as a guide for risk management in MHP projects in Indonesia. It is hoped that the design of this strategy will also help the project to achieve its goals. Furthermore, the results of this research can be used as learning materials in planning the development of MHP in the future.